Pharmacological Modulation of the Psychiatric Risk Factor FKBP51 Alters Efficiency of Common Antidepressant Drugs - Pöhlmann, Max L.; Häusl, Alexander S.; Harbich, Daniela; Balsevich, Georgia; Engelhardt, Clara; Feng, Xixi; Breitsamer, Michaela; Hausch, Felix; Winter, Gerhard; Schmidt, Mathias V. (Frontiers in Behavioral Neuroscience, 2018)
Despite a growing body of research over the last few decades, mental disorders, including anxiety disorders or depression, are still one of the most prevalent and hardest to treat health burdens worldwide. Since pharmacological treatment with a single drug is often rather ineffective, approaches such as co-medication with functionally diverse antidepressants (ADs) have been discussed and tried more recently. Besides classical ADs, there is a growing number of candidate targets identified as potential starting points for new treatment methods. One of these candidates, the FK506 binding protein 51 (FKBP51) is linked to a number of psychiatric disorders in humans. In this study, we used SAFit2 - a newly developed modulator of FKBP51, which has shown promising results in rodent models for stress-related disorders delivered in a depot formulation. We combined SAFit2 with the commonly prescribed selective serotonin reuptake inhibitor (SSRI) escitalopram and performed basic behavioral characterization in a mouse model. Remarkably, co-application of SAFit2 lowered the efficacy of escitalopram in anxiety-related tests but improved stress coping behavior. Given the fact that mental diseases such as anxiety disorders or depression can be divided into different sub-categories, some of which more or less prone to stress, SAFit2 could indeed be a highly beneficial co-medication in very specific cases. This study could be a first, promising step towards the use of FKBP51 modulators as potent and specific enhancers of AD efficiency for subclasses of patients in the future.